Sustainable Agriculture in Peru Based on Agrobiodiversity and Climate-Smart Agriculture – Evaluation of a Case Study with Small Farmers in an Andean Basin - Aguilar-luis, Miguel Angel (2024)
The loss of biodiversity and the effects of climate change hurt agricultural production and food security in Peru and around the world. The family farming sector in Peru (97% of agricultural units – AU) faces numerous challenges when it comes to sustainably producing food. To sustain Peruvian agriculture in the face of climate change, climate-smart agricultural (CSA) practices and agrobiodiversity conservation are essential. This document characterizes the level of agrobiodiversity (index IDA) of family AUs in the Crisnejas basin and analyzes the impact of the elements that affect farmers’ decisions to apply multiple CSA measures. CSA adoption decisions were analyzed using an econometric analysis framework combining multivariate and ordered probit models for 340 family AUs. Results indicate that AUs with a lower agrobiodiversity index (IDA) have a higher monthly income (IDA = 0.56, 312 USD, Pearson binary correlation, CI = -0.4107). The highest economic income AUs are located between 2,500 and 3,000 meters above sea level (352 USD, CI = -0.3551), have access to irrigation (365 USD, CI = -0.5225), and are also part of consolidated family farms (428 USD, CI = -0.2699). Based on the econometric results, farmers’ decisions to adopt CSA practices are influenced by altitude, tenure, age, cultivated area, level of agrobiodiversity, and access to water. A larger number of household members, a better educational level, and a greater distance to the local market increase the probability of intensifying the use of CSA practices in the lower, middle, and upper basins, respectively (significant coefficient estimates, p-value < 0.05). Distance to the farms, cultivated area, and seed storage are other factors associated with the intensity of CSA use (p-value < 0.05). According to the findings, agrobiodiversity must be increased in Peruvian agriculture to achieve a functional and balanced system from an economic, ecological, and sociocultural perspective, as well as carefully developing adaptation/mitigation strategies to address the impacts of climate change on Peruvian agriculture.